2014
DOI: 10.1167/iovs.14-13973
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Recovery of Cone Outer Segment Tips Line and Foveal Displacement After Successful Macular Hole Surgery

Abstract: The restoration of the temporal COST line was delayed after successful macular hole surgery. In addition, the fovea was displaced more nasally than the center of the COST line defect which recovered centripetally. (ClinicalTrials.gov number, NCT01959776.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Several studies have demonstrated a displacement of the fovea toward the optic disk after ILM peeling 1013,15. The present three cases also showed a reduction in the papillofoveal distances, suggesting that a centripetal retinal movement and retinal displacement toward the optic disk may have occurred simultaneously.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Several studies have demonstrated a displacement of the fovea toward the optic disk after ILM peeling 1013,15. The present three cases also showed a reduction in the papillofoveal distances, suggesting that a centripetal retinal movement and retinal displacement toward the optic disk may have occurred simultaneously.…”
Section: Discussionsupporting
confidence: 65%
“…Movements of the retinal tissues associated with ILM peeling are well recognized to occur after treatment for several retinal diseases such as MH,913 ERM,14 and diabetic macular edema 15. These retinal movements may contribute to the healing processes after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Alterations in the retinal microstructure and structural stability due to ILM peeling have been postulated as a reason for nasal displacement of retina after MH surgery with ILM peeling. [15][16][17][18] The changes in retinal microstructure found in our study may also be partially caused by an alteration in structural stability due to ILM peeling. The frequency of the notching of tissue as well as the amount of foveal tissue elongation were relatively greater in the nasal direction, suggesting these phenomena may have some association with nasal displacement of the retina, as was reported in previous studies.…”
Section: Discussionmentioning
confidence: 60%
“…These cases were presumably congenital and developmental anomalies. Foveal displacement may be associated with intraocular surgeries such as retinal detachment or macular hole surgeries [6][7][8] . In a study performed Kawano et al [8] after vitrectomy with ILM peeling for macular hole, fovea of the patients displaced toward the optic disc.…”
Section: Discussionmentioning
confidence: 99%